Modern approach in functional assessment of adaptation of athletes with heart rhythm disorders - V.F. Lutkov; L.L. Miller; G.I. Smirnov; D.I. Shadrin (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify types of heart rhythm migration disorders and their impact on the adaptation of athletes with foci of chronic infection and signs of maladaptation. Methods and structure of the study. 421 athletes of qualification from the 1st category to the master of sports were examined. A comprehensive medical and functional examination included clinical and instrumental methods of examination (ECG, RKS-01 Rhythmocardioscope). The health status of the athlete, the electrical function of the heart were assessed, heart rhythm disturbances were detected, the index of the functional state was calculated according to the parameters of the correlation rhythmogram. Results and conclusions. One of the tasks of monitoring the functional state of athletes is to identify early signs of overstrain syndrome (stress damage to the heart), which occurs in them under conditions of inconsistency of physical activity with the functional adaptive reserve of the body. The article substantiates the expediency of using a special technique: electrocardiography and correlation rhythmography to identify types of pacemaker migration and calculate the functional state index for athletes with heart rhythm disturbances. Indicators of active and passive types are combined with a decrease in the index of the athlete’s functional state, they are harbingers of cardiac pathology that develops with excessive physical exertion and lead to a decrease in the athlete’s performance.